Direct Strong Acid Copper Plating on Steel Substrate without Pre - Plating - ZHANG Zhi-liang, ZHANG Ying (Cailiao Baohu)
The acid copper plating on steel substrate required pre-plating to ensure the adhesion between coating and substrate, which not only increased the process flow but also increased the resource consumption. By introducing surface active substances, a process for direct strong acid copper plating on steel substrate was developed, which could be used for direct strong acid copper plating on steel substrate without pre-plating. From the test results, the coating prepared by this process had good adhesion, its adhesion to the substrate could meet the requirements of product performance. The reason why this process could directly conduct copper plating on the steel substrate in strong acidic environment was that the strong surface-active substances was combined in the additive, so that the replacement of copper ions and iron atoms could be carried out orderly, thus ensuring the adhesion between the copper coating and the steel substrate.